Domestic Violence Work at Columbia Law School - LaVelle, Laura (Columbia Journal of Gender and Law, 1998)
The Domestic Violence Project (DVP) at Columbia Law School was founded in 1994 by a third-year law student, Maxine Rosenthal. In its early years, the Domestic Violence Project provided law students with the opportunity to advocate in Family Court for battered women through a court accompaniment program. Through this program, Victim Services Westside Office Legal Project would send an attorney every semester to train Columbia law students. Then, Victim Services would call Columbia’s DVP hotline when they needed a student to accompany an otherwise unrepresented woman seeking an Order of Protection in Family Court. Usually women whom students accompanied to court had already spent a day in court filing for and obtaining a temporary Order of Protection. In an accompaniment case, students would interview women before their upcoming adjourn dates and advocate for them in hearings for their final Orders of Protection before Family Court judges. The students’ moral support and advocacy provided women with needed assistance at a crucial point in their cases. The DVP continues today to take these accompaniment cases from Victim Services and other legal agencies.